4D Seismic Monitoring in Highly Populated Area: Study of CCUS in Sukowati Oil Field, East Java - Oki Hedriana; Rachmat Sule; Wawan Gunawan A. Kadir; Asep K. Permadi; Djoko Santoso; Junita Trivianty; Dewi Mersitarini; Dimas Ardiyanta; Sofyan Sumarna (Scientific Contributions Oil and Gas, 2025)
Indonesia is resolutely addressing climate change with a commitment to reduce carbon emissions by 29% in 2030, and we are on track to achieve net-zero emissions in 2050. This country acknowledges the important role of Carbon Capture, Utilization, and Storage (CCUS) in mitigating carbon emissions, especially from the energy sector, and at the same time increasing oil and gas production. This kind of approach is also well known as CO2-EOR (Enhanced Oil Recovery) and CO2-EGR (Enhanced Gas Recovery). Sukowati field is situated in the East Java Province and will serve as a pioneering CO2 Enhanced Oil Recovery (EOR) project aimed at revitalizing the field. This initiative focuses on increasing oil production while capturing and storing carbon dioxide (CO2), contributing to environmental sustainability. To ensure its success, a robust monitoring system must be implemented for real-time data collection and analysis, optimizing recovery processes and minimizing environmental impact. Monitoring activities deliver information regarding the CO2 injected into the reservoir and the risk of leakage into the surrounding injection region. Several methods are discussed for monitoring CO2 plumes, but in the subsurface, seismic methods stand out as the most promising option. However, despite their effectiveness, seismic methods are also among the most expensive to execute, necessitating significant investment in technology and expertise to ensure accurate and reliable data. 4D seismic, also known as time-lapse seismic, entails performing repeated seismic surveys over a designated area to monitor changes in the subsurface effectively. This imaging technique enables us to visualize the movement of CO2 plumes within the target formation and can identify alterations in the reservoir that may suggest a potential CO2 leak. A seismic survey before the injection is needed to create a baseline image of the subsurface target reservoir. Changes in velocity and amplitude are identified when the seismic waves encounter the CO2 plumes injected into the reservoir target. The challenges of performing a 4D seismic imaging survey in a densely populated area are social impact, the possibility of damaging infrastructure, high noise levels, and high operating costs, particularly if it uses a subterranean explosive (dynamite) as a source of seismic signals. To address these challenges, the study introduces a novel approach to designing irregular 4D seismic surveys. This method features a flexible acquisition layout that departs from traditional geometric symmetry. The survey utilizes a non-impulsive (vibrator) of semi-permanent seismic source and a highly sensitive, wireless seismic recording system. The irregular design is adaptively tailored based on the field's spatial characteristics, potential surface disruptions, and cost considerations. Despite not adhering to a conventional grid or orthogonal configuration, this approach ensures adequate offset and azimuth coverage necessary for detecting subsurface changes.